Staying at Home: The Perspectives of Minangkabau Ulemas Concerning Husbands' Provision of Sustenance in Covid-19 Impacted Households - Fatahuddin Aziz Siregar; Azhari Akmal Tarigan; Nofialdi Nofialdi; Febri Yulika; Iswandi Syahputra; Nurhayati Nurhayati; Benny Ridwan (Institut Agama Islam Negeri Batusangkar, 2022)
The article discusses the perspectives of Minangkabau ulemas in West Sumatra concerning the ruling for husbands incapable of providing a living for their wife as a result of the COVID-19 pandemic. In West Sumatra, some husbands were unable to provide sustenance to their wife because they were dismissed from their employment due to the COVID-19 pandemic. The study findings are highly specific as Minangkabau customs and culture are grounded on a matrilineal system, yet they remain to be based on Islamic sharia. The research data were acquired by in-depth interviews with three influential ulemas in West Sumatra and a prominent customary figure who is the Chair of the Minangkabau Adat Council. The study found that according to the Minangkabau customary and cultural perspective, husbands are duty-bound to earn a living outside their home while their wife remains at home. Such spousal relationship has an impact on the wife’s acceptance of the husband who became jobless since they were dismissed on account of the pandemic. A condition wherein wives can accept being married to a husband incapable of providing a living on account of the COVID-19 outbreak does not become a legal issue. Accordingly, the study will have implications on the formation of new categories concerning the husband’s obligation to provide sustenance to his wife during a state of emergency.